Risk factors and prognosis analysis of dysphagia after occipitocervical fusion surgery: a retrospective study of 43 cases - Yufan Chen; Weihong Xu (Journal of Orthopaedic Surgery and Research)
Abstract Objectives To analyze the risk factors for developing dysphagia after occipitocervical fusion (OCF) and investigate possible mechanisms and prognosis. Methods The case data of 43 patients who underwent OCF were retrospectively reviewed. Patients were divided into group A (dysphagia group) and group B (non-dysphagia group) based on Bazaz scoring criteria. Baseline data and imaging parameters were collected: O-C2 angle, C2-7 angle, pharyngeal inlet angle (PIA), posterior occipital cervical angle (POCA), O-EA angle, Oc-Ax angle, Atlas-dens interval, C2-7 sagittal vertical axis (SVA), T1 slope, narrowest oropharyngeal airway space (nPAS), and thickness of the prevertebral soft tissue. Potential risk factors were identified via one-way intergroup comparisons and included in multivariable logistic regression analysis. Pearson or Spearman correlation analysis was performed to assess associations between dnPAS% and each parameter and inter-parameter correlations. Predictors were selected to plot receiver operating characteristic (ROC) curves for diagnostic evaluation. Prognosis was analyzed using the Kaplan-Meier method and curvilinear regression. Results Dysphagia occurred in 17 of 43 patients (39.53%). By the final follow-up (≥ 12 months), 11 patients (25.58%) had residual symptoms. Baseline factors, including dyspnea (P = 0.028), operative segment (P = 0.021), operative time (P = 0.006), anesthesia time (P = 0.025), solitude (P = 0.019), and satisfaction (P < 0.001), differed significantly between groups. Imaging parameters dO-C2a (P < 0.001), dPOCA (P < 0.001), PoPIA (P = 0.036), dPIA (P < 0.001), dOc-Axa (P = 0.001), dC2-7 SVA (P = 0.040), PonPAS (P = 0.004), dnPAS (P = 0.005), and dnPAS% (P < 0.001) were also significantly different. Multivariable regression analysis identified dPIA (OR = 0.870, P = 0.008) as an independent protective factor. ROC analysis showed dPIA had good diagnostic value (AUC = 0.855) with a cutoff of -8°. Prognostic analysis indicated rapid recovery was possible by 3 months postoperatively, with full recovery achieved in ~ 30% of patients by 1 year, after which recovery plateaued. Conclusion Postoperative dysphagia after OCF appears to result from multiple factors involving both “static + dynamic” elements. dPIA is a reliable predictor, with patients having a dPIA >-8° being less likely to develop dysphagia. However, only ~ 30% of patients achieve full recovery.